Application for the Suspension of the Execution of Judgment No 2867 Filed by the International Fund for Agricultural Development. (2016) - Unknown
Abstract : 18 International organizations — Staff — Appeals mechanism — International Labour Organization Administrative Tribunal — Provision for challenge to judgment of the Tribunal by request to International Court of Justice for advisory opinion — Request for suspension of execution of judgment pending opinion — Admissibility of request — Powers of the Tribunal in the absence of express provisions in statute — Impossibility of tribunal assessing soundness of its own judgments — Imbalance in rights of the parties International Court of Justice — Advisory jurisdiction — International staff cases — Challenge to judgment of International Labour Organization Administrative Tribunal — Stay of execution of judgment pending opinion